DOES XBRL IMPROVE THE QUALITY OF FINANCIAL STATEMENTS IN THE BANKING INDUSTRY? - Prasetyo, Hari; Apandi, Nelly Nur (Fakultas Pendidikan Ekonomi dan Bisnis, 2019)
This study aims to determine the influence of the complexity of the banking business on the quality of financial statements that are moderated by the XBRL reporting form on the banking industry sector listed on the Indonesia Stock Exchange in 2017. The sample used was 43 banking companies from a total of 91 financial sector companies, based on purposive sampling. The complexity of the banking business in this study is measured by the level of complexity of the BOOK based on OJK regulations No. 6 / POJK.03 / 2016, the quality of financial statements is measured using non discretionary accruals and xbrl is measured by the use of the company in that year. In analyzing data, this study uses statistical tests of multiple regression analysis. Based on the calculation of multiple regression analysis with the help of Eviews 10 software, the relationship between the complexity of the banking business and the quality of financial statements is strengthened by the form of XBRL reporting